Experiences of African international students in a South African university – A qualitative study - Kasese-Hara, M.; Mugambi, J. I. (South African Journal of Higher Education, 2021)
South Africa has in latter decades embraced the growing trend of internationalization in higher education leading to greater international mobility of staff and students. Compared to other countries in most of the sub-Saharan Africa region, South Africa has a larger capacity to meet the tertiary needs of students within the region. An increasing number of international students has implications for their academic success, adaptation and wellbeing once in their host country. The current study explored the lived experiences of international students in a South African university, from 5 other African countries. The study adopted a qualitative design, using semi-structured in-depth interviews and open-ended questions. Nine mainly postgraduate students (4 males and 5 females) were recruited using convenient and snowball sampling methods. Data were analysed using thematic content analysis and revealed 5 themes namely “Internationalisation”, “experiencing the unforeseen”, “access”, “social support” and “structural support”, with several sub-themes emerging from these. A resulting framework shows “empowerment”, “alienation” and “adaptation” as over-arching themes in experiencing the phenomenon of being an African foreign student in South Africa.